Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1007/s10593-005-0214-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitropyridines. 2. Hantzsch Synthesis of Nitro- and Dinitropyridines

Abstract: The interaction of α,β-unsaturated nitro ketones and various enamines leads to the synthesis of 5-nitro-1,4-dihydropyridines containing acetyl, amide, benzoyl, ester, and cyano groups in position 3, and also unsymmetrical 3,5-dinitro-1,4-dihydropyridines. Aromatization of the nitrodihydropyridines was carried out with sodium nitrite in acetic acid.The synthesis of nitropyridines by the Hantzsch reaction is effected by the cyclocondensation of α,β-unsaturated nitro ketones (condensation products of aromatic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…With 4-arylated dinitro-DHPs in hand, we carried out preliminary studies on the oxidative conversion of 4-substituted DHPs to 4-substituted-3,5-dinitropyridines, which are not easily accessible by other methods. 13 As shown in Scheme 6, treatment of 4-anisyl DHP 3Bb with excess amount of NaNO 2 in chloroform under oxygen atmosphere at 80 C for 24 h to afford the desired product 7 in a promising isolated yield of 68%. The obtained 4-arylated-3,5-dinitropyridines are useful synthetic intermediates for functional materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With 4-arylated dinitro-DHPs in hand, we carried out preliminary studies on the oxidative conversion of 4-substituted DHPs to 4-substituted-3,5-dinitropyridines, which are not easily accessible by other methods. 13 As shown in Scheme 6, treatment of 4-anisyl DHP 3Bb with excess amount of NaNO 2 in chloroform under oxygen atmosphere at 80 C for 24 h to afford the desired product 7 in a promising isolated yield of 68%. The obtained 4-arylated-3,5-dinitropyridines are useful synthetic intermediates for functional materials.…”
Section: Resultsmentioning
confidence: 99%
“…13 As shown in Scheme 6, treatment of 4--anisyl DHP 3Bb with excess amount of NaNO 2 in chloroform under oxygen atmosphere at 80 °C for 24 h to afford the desired product 7 in a promising isolated yield of 68%. The obtained 4--arylated--3,5--dinitropyridines are useful synthetic intermediates for functional materials.…”
mentioning
confidence: 99%
“…Results revealed that pyrroles unsubstituted at positions 2 and 5 are the most active. Similarly, 1,4‐dihydropyridines were also prepared from α‐nitrochalcones as shown in reaction 8, Figure 31 [137] . Aromatization of the obtained nitrodihydropyridines was carried out with sodium nitrite in acetic acid to give pyridines.…”
Section: Different α‐Substituted Chalconesmentioning
confidence: 99%
“…Aiming to expand a number of promising quinoxaline and oxazine derivatives and to study their pharmacological activities, we synthesized similar compounds using the example of 1-(5-nitropyridin-3-yl)ethan-1-one derivative. 1-[4-(furan-2-yl)-2-methyl-5-nitro-6-phenylpyridin-3-yl]ethan-1-one 18 (3) was chosen as an initial object for our study. The presence of pyridine core and pharmacophore functions such as nitro group and furan ring, as well as reactive acetyl group in the molecule of 5-nitro-6-phenylpyridine 3 opens the way to its modification.…”
mentioning
confidence: 99%